2016
DOI: 10.1111/neup.12313
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic and meningothelial meningiomas in a single tumor: A “dedifferentiated meningioma”?

Abstract: The patient was a 74-year-old man, who developed progressive cognitive impairment and gait instability. Neuroradiological examination demonstrated a large and predominantly extra-axial tumor spreading over the bilateral frontal base, indicative of olfactory groove meningioma. The greater part of the resected tumor consisted of a dense, patternless proliferation of large, round or polygonal cells, and compactly fascicular growth of spindle cells. Tumor cells showed markedly anaplastic cytological features. In s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The term "dedifferentiated meningioma" was recently proposed for the existence of anaplastic and low-grade components in a single meningeal tumor. 15,16) In our case, both subtypes were low grade, not indicating dedifferentiated meningioma.…”
Section: Nmc Case Report Journal Vol8 2021mentioning
confidence: 46%
“…The term "dedifferentiated meningioma" was recently proposed for the existence of anaplastic and low-grade components in a single meningeal tumor. 15,16) In our case, both subtypes were low grade, not indicating dedifferentiated meningioma.…”
Section: Nmc Case Report Journal Vol8 2021mentioning
confidence: 46%
“…[4] Shintaku et al reported the dedifferentiation of meningioma with histopathological analysis showing anaplastic and meningothelial meningioma components juxtaposed. [19] Similarly, Osipov et al reported a case of radiation-induced dedifferentiation of a meningioma into an osteosarcoma. [13] Histopathological analysis showed features of a malignant meningioma adjacent to that of an osteosarcoma.…”
Section: Discussionmentioning
confidence: 95%
“…reported the dedifferentiation of meningioma with histopathological analysis showing anaplastic and meningothelial meningioma components juxtaposed. [ 19 ] Similarly, Osipov et al . reported a case of radiation-induced dedifferentiation of a meningioma into an osteosarcoma.…”
Section: Discussionmentioning
confidence: 99%